Enhancing Tourist Experience at Ponot Waterfall with a Mobile E-Ticket Application Using FAST Methodology - Nisa, Khairrun; Yahfizham, Yahfizham (Universitas Bina Darma, 2025)
Technology played a crucial role in tourism management, particularly through mobile-based e-commerce, which facilitated transactions. This sector supported national development by creating business opportunities, employment, and promoting cultural preservation and environmental sustainability. Ponot Waterfall, located in Tangga Village, Aek Songsongan, Asahan, became a tourist destination due to its natural beauty and conservation efforts. However, the manual ticketing system often led to long queues and inconvenience, especially during holiday seasons. Additionally, the use of paper-based tickets posed environmental pollution risks. As the number of tourists increased, an application-based e-ticketing system emerged as a solution for accessing ticket information, making purchases, and processing online payments. This study aimed to develop a mobile e-ticketing application for Ponot Waterfall using the FAST method to optimize user needs and enhance the visitor experience in e-ticketing system development. The goal was to improve purchasing efficiency, reduce queues, and enhance the overall visitor experience. The application facilitated information access, supported online payments, improved tourism management, and minimized the environmental impact of paper-based ticketing. The results of this study indicated that the mobile-based e-ticketing application at Ponot Waterfall successfully enhanced transaction efficiency, reduced long queues, eliminated the use of paper tickets, and simplified access to tourism information. The majority of users utilized online ticket booking and digital payment methods as the primary features, proving that the system effectively addressed the challenges associated with the previous manual system.